ANALISIS STRATEGI BAZNAS ENREKANG DALAM MELAKUKAN MONITORING DAN EVALUASI KEPADA ALUMNI PELATIHAN OTOMOTIF - Rusman, Haerusman; Hatta, M. (Komunitas Manajemen Kompetitif, 2024)
The era of globalization and technological advancement has driven the growth of the automotive sector as one of the strategic pillars in meeting mobility needs and improving the community's economy. The high interest of the Enrekang community in private vehicles creates opportunities as well as challenges in the form of the need for competent automotive workers. Responding to this challenge, BAZNAS Enrekang organizes an automotive training program based on community empowerment by integrating Islamic values ​​and a holistic approach. This study aims to analyze the monitoring and evaluation strategies implemented by BAZNAS towards automotive training alumni. The research method uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results of the study indicate that monitoring strategies, such as direct visits, online communication and periodic reporting, have a positive impact on supporting the sustainability of alumni skills. Alumni who received intensive assistance succeeded in developing independent businesses, although challenges such as limited resources, geographical constraints and lack of technological innovation are still obstacles. This study aims to analyze the monitoring and evaluation strategies implemented by BAZNAS towards automotive training alumni. The research method uses a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results of the study indicate that monitoring strategies, such as direct visits, online communication and periodic reporting, have a positive impact on supporting the sustainability of alumni skills. Alumni who received intensive assistance succeeded in developing independent businesses, although challenges such as limited resources, geographical constraints and lack of technological innovation are still obstacles.